Does the gene matter? Genotype–phenotype and genotype–outcome associations in congenital melanocytic naevi. (9th August 2019) - Polubothu, S.; McGuire, N.; Al‐Olabi, L.; Baird, W.; Bulstrode, N.; Chalker, J.; Josifova, D.; Lomas, D.; O'Hara, J.; Ong, J.; Rampling, D.; Stadnik, P.; et al.
Summary: Background: Genotype–phenotype studies can identify subgroups of patients with specific clinical features or differing outcomes, which can help shape management. Objectives: To characterize the frequency of different causative genotypes in congenital melanocytic naevi (CMN), and to investigate genotype–phenotype and genotype–outcome associations. Methods: We conducted a large cohort study in which we undertook MC1R genotyping from blood, and high‐sensitivity genotyping of NRAS and BRAF hotspots in 156 naevus biopsies from 134 patients with CMN [male 40%; multiple CMN 76%; projected adult size (PAS) > 20 cm, 59%]. Results: Mosaic NRAS mutations were detected in 68%, mutually exclusive with BRAF mutations in 7%, with double wild‐type in 25%. Two separate naevi were sequenced in five of seven patients with BRAF mutations, confirming clonality. Five of seven patients with BRAF mutations had a dramatic multinodular phenotype, with characteristic histology distinct from classical proliferative nodules. NRAS mutation was the commonest in all sizes of CMN, but was particularly common in naevi with PAS > 60 cm, implying more tolerance to that mutation early in embryogenesis. Facial features were less common in double wild‐type patients. Importantly, the incidence of congenital neurological disease, and apparently of melanoma, was not altered by genotype; no cases of melanoma were seen in BRAF ‐mutant multiple CMN, however, this genotype is rare. Conclusions: CMN of all sizes are most commonly caused by mutations in NRAS . BRAF is confirmed as a much rarer cause of multiple CMN, and appears to be commonly associated with a multinodular phenotype. Genotype in this cohort was not associated with differences in incidence of neurological disease in childhood. However, genotyping should be undertaken in suspected melanoma, for guidance of treatment. What's already known about this topic? Multiple congenital melanocytic naevi (CMN) have been shown to be caused by NRAS mosaic mutations in 70–80% of cases, by BRAF mosaicism in one case report and by inference in some previous cases. There has been debate about genotypic association with different sizes of CMN, and no data on genotype–outcome. What does this study add? NRAS mosaicism was found in 68%, BRAF in 7% and double wild‐type in 25% of cases of CMN. NRAS was the commonest mutation in all sizes of CMN, but was nearly universal in projected adult size > 60 cm. BRAF is often associated with a distinct multinodular clinical/histological phenotype. Adverse outcomes did not differ between genotypes on current numbers. Abstract : Plain language summary available online